A novel approach towards green synthesis of silver nanoparticles from Bignonia Venusta (L.) for their biocompatibility studies. (Funded work) - MANOJ SHARMA,; SEEMA INDORA,; R.D. AGRAWAL, (International Journal of Pharma and Bio Sciences, 2017)
In recent years, the green synthesis of nanoparticles using various plant extracts has attracted great attention as these methods are simple, inexpensive and, eco-friendly. In the present investigation an attempt has been made for green synthesis of silver nanoparticles using plant extracts of Bignonia venusta (L.). In this study, it was observed that the plant extracts lead to the formation of crystalline silver nanoparticles. Bignonia venusta (L.) is known as a rich source of flavonoids, steroids, tannins and other phenolic compounds. The AgNPs prepared by green synthesis methods were monitored by measurements of FT-IR. Further morphology and size were determined by SEM and TEM. The size of AgNPs varied between 50 nm and 100 nm. XRD was done to study diffraction which denotes crystal structure of AgNPS. The AgNPs were tested for antimicrobial, antioxidants activity. Maximum antimicrobial activity was observed against Streptomyces grisveus at 40 µg/ml (20 mm) while in fungus no activity was observed.